Menjaga keseimbangan integrasi manajemen risiko dan kepatuhan syariah di sektor perbankan syariah Indonesia - Wicaksono, Naufal Rizki (Maliki Interdisciplinary Journal, 2024)
Risk management has an important role in the banking industry, especially in the context of sharia banking in Indonesia. This article discusses effective risk management strategies in dealing with operational, credit, market risks and compliance with sharia principles. This strategy includes risk identification, risk evaluation and risk management by taking into account sharia principles. The implementation of information technology is also a key part of this strategy, helping Islamic banks identify and respond to risks more quickly and accurately.Government regulations and policies also play an important role in Islamic banking risk management strategies in Indonesia. Islamic banks need to continuously update their strategies to comply with applicable regulations and maintain compliance with sharia principles. In addition, other internal and external factors, such as flexibility in responding to changes in the external environment and cooperation with regulators, also need to be considered. Thus, the risk management strategy for sharia banking in Indonesia must be holistic, integrated, and prioritize compliance with sharia principles to ensure the sustainability and growth of sharia banks.